Новые исследования курганного могильника у с. Купьеваха - Бойко, Ю.Н. (My University, 2008)
Boyko Y. New Researches of Burial Mounds Near Kupyevakha Village In the publication the materials of the last researches of the Scythian burial mounds near Kupyevakha village Kharkov region are introduced into the scientific circulation (burial mounds # 21–25). The obtained data confirm earlier made conclusions about gradual transformation of burial constructions during the Scythian period: from lengthened-rectangular burial diggings of the earlier period to almost square with inner burial timber constructions in the later times. By the beginning of the IV century BC the prevailing orientation of the deceased heads changes from the West to the South. In the equipment composition the moulded earthenware proportion reduces at the expense the Antic ceramics usage. The complex constructions with religious-priestly functions are marked (burial mound # 21). The absolute absence of horse equipment fragments and beast-style decorated things is noticed inside the burials.